Root Carbon Resources Determine Survival and Growth of Young Trees Under Long Drought in Combination With Fertilization - Yang, Yue; Ouyang, Shengnan; Gessler, Arthur; Wang, Xiaoyu; Na, Risu; He, Hong S.; Wu, Zhengfang; Li, Mai-He (Frontiers in Plant Science, 2022)
Current increases in not only the intensity and frequency but also the duration of drought events could affect the growth, physiology, and mortality of trees. We experimentally studied the effects of drought duration in combination with fertilization on leaf water potential, gas exchange, growth, tissue levels of non-structural carbohydrates (NSCs), tissue NSC consumption over winter, and recovery after drought release in oak (Quercus petraea) and beech (Fagus sylvatica) saplings. Long drought duration (> 1 month) decreased leaf water potential, photosynthesis, and NSC concentrations in both oak and beech saplings. Nitrogen fertilization did not mitigate the negative drought effects on both species. The photosynthesis and relative height increment recovered in the following rewetting year. Height growth in the rewetting year was significantly positively correlated with both pre- and post-winter root NSC levels. Root carbon reserve is critical for tree growth and survival under long-lasting drought. Our results indicate that beech is more sensitive to drought and fertilization than oak. The present study, in a physiological perspective, experimentally confirmed the view that the European beech, compared to oak, may be more strongly affected by future environmental changes.